Paclitaxel Priming of TRAIL Expressing Mesenchymal Stromal Cells (MSCs- TRAIL) Increases Antitumor Efficacy of Their Secretome - Coccè, Valentina; Bonomi, Arianna; Cavicchini, Loredana; Sisto, Francesca; Giannì, Aldo; Farronato, Giampietro; Alessandri, Giulio; Petrella, Francesco; Sordi, Valeria; Parati, Eugenio; Bondiolotti, Gianpietro; Paino, Francesca; et al. (Current Cancer Drug Targets, 2021)
Background: Adipose tissue-derived MSCs engineered with the tumor necrosis factor- related apoptosis-inducing ligand protein (MSCs-TRAIL) have significant anticancer activity. MSCs, without any genetic modifications, exposed to high doses of chemotherapeutic agents are able to uptake the drug and release it in an amount affecting tumor proliferation. The purpose of this study was to verify the ability of MSCs-TRAIL to uptake and release paclitaxel (PTX) by providing an increased antitumor efficacy. Methods: MSCs and MSCs-TRAIL were tested for their sensitivity to Paclitaxel (PTX) by MTT assay, and the cells were loaded with PTX according to a standardized procedure. The secretome was analysed by HPLC for the presence of PTX, microarray assay for soluble TRAIL (s-TRAIL) and tested for in vitro anticancer activity. Results: MSCs-TRAIL were resistant to PTX and able to incorporate and then release the drug. The secretion of s-TRAIL by PTX loaded MSCs-TRAIL was not inhibited, and the PTX delivery together with s-TRAIL secretion resulted in increased antitumor efficacy of cell secretome as tested in vitro on human pancreatic carcinoma (CFPAC-1) and glioblastoma (U87-MG). Conclusion: Our result is the first demonstration of the possible merging of two new MSCs therapy approaches based on genetic manipulation and drug delivery. If confirmed in vivo, this could potentiate the efficacy of MSCs-TRAIL and strongly contribute to reducing the toxicity due to the systemic treatment of PTX.
Keywords: U87-MG